Економіко-екологічні аспекти організації території екологічно чистих сільськогосподарських земель - Tiutiunnyk, Hanna (Dr. Viktor Koval, 2018)
Introduction. The foundation of the creation of ecologically clean land masses is the economic organization of the territory. The leading component of ecologically safe land use is the need to determine the suitability of land soils for the cultivation of raion crops and the maintenance of maximum soil quality adapted to the quality of crop rotation. Aim and tasks. In the article the purpose of planning the organization of land mass structures is determined. The task of the internal land management is to formulate a strategy for using land masses that would maximally focus on the actions of land users in optimizing, transforming and using land to the natural conditions of the region. Research results.  Measures to create ecologically pure land masses are carried out directly at agricultural enterprises, therefore, agricultural land use is a prerequisite for them. The organization of agricultural land use envisages for business entities, the establishment of a warehouse, the transformation of lands and conservation of degraded and low productivity land, which at the present stage has become the most effective factor in the environmental optimization of land use. Agroecological organization of the territory includes measures on four systemic properties of agroecosystems: productivity, stability, stability and uniformity. All four properties are interrelated in agroecosystems. Without these links it is impossible to organize the territory in order to create conditions for rational use and protection of land, which is demanded by the agricultural land management system. Conclusion. In the article the necessity of characterization of qualitative and quantitative characteristics of lands is grounded in order to find out the influence of the creation of the land mass and the appearance of possible dangers. The basic stages of the transition to environmentally safe agriculture and the formation of ecologically clean land masses have been determined. The types of development of the land mass are described: one-time and step-by-step. The complex problems that may be encountered by an enterprise of any ownership type in the transition to the maintenance of ecologically pure agriculture are determined. Creation of ecologically pure massifs of lands and agroecological organization of the territory includes a system of measures for the adaptation of agricultural production, agriculture to the peculiarities of the natural environment, along with the system of levers of state management of rational ecologically safe use of agricultural land. So the necessity of state support and motivation for enterprises planning to switch to the production of ecologically clean products and the formation of ecologically clean land masses has been substantiated.